Inclusive and Exclusive Perceptions of Difference. Native and Euro Based Concepts of Time, History, Change - Doxtator, Deborah (Decentring the Renaissance: Canada and Europe in Multidisciplinary Perspective 1500–1700, 2001)
In 1558, confronted by the differences in the ways Native peoples and Europeans perceived and structured their respective societies, Renais- sance travel writer Andre Thevet asserted that the indigenous popula- tions of North America, unlike Europeans, had neither religion, civility, nor books, and lived like 'beasts without reason' (Thevet [1558] 1878, 134-6). In 1603, writing of the Native groups he encountered, Samuel de Champlain remarked that since each person 'prayed in his heart just as he liked,' they in effect had 'no law among them and do not know what it is to worship God and pray to Him, living as they do like brute beasts' (Champlain 1922-36, 6: 52). In contrast, Native groups, although not always conciliatory, nonetheless sought out ways to incorporate Europeans into existing political and ideological structures, inviting Champlain, Jesuit missionaries, and others to come to live with them and to participate in their way of life (Dickason 1992, 103, 107).A funda- mental element of Rotinonhsyonni1 diplomacy was the political neces- sity to achieve integrations so that, at least ideologically, Europeans and Iroquoians could perceive themselves to be brothers, one and the same people (Jesuit Relations [1610-1791] 1896-1901 [hereafter JR] 27: 253- 61). When Jacques Cartier encountered the Montagnais-Naskapi in 1534, he remarked on their ease of manners in their coming 'freely on board our vessels as if they had been Frenchmen' (Cartier 1924, 76).
Pages: 33-47
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé